Employee engagement: what is it and how do we go about it? - Abu Bakar, R. (2014)
Although numerous scholars has improved our understanding of the implications of engagement, relatively little attention has been paid to its conceptual definition. This paper provides a conceptual review of its definition and examined the contextual characteristics that define engagement. Specifically, the paper discusses some debatable meaning of engagement that yields inconsistent views from scholars. Based on the review, this paper found that engagement focuses upon the positive and fulfilling aspects of doing work. For a person to be engaged, he or she must be vigorous, dedicated and absorbed in their job. This positive reflection is in line with the movement of positive organizational behavior in seeking to understand how individuals thrive at work.